Potret Pendidikan Islam Feminis (Studi Kasus di FTK UIN Sunan Ampel) - Fahmi, Muhammad; Sadieda, Lisanul Uswah; ALfiyah, Hanik Yuni (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This article successfully portrayed feminist Islamic education (Islamic education with a female face) at the Faculty of Tarbiyah and Teacher Training at the Sunan Ampel State Islamic University FTK UINSA Surabaya. Through qualitative studies, the following exposure results were found. First, Islamic education at FTK UIN Sunan Ampel has a female face (Islamic feminine education). In the sense that the number of female students is more dominant compared to male students. This is related to the prospect of FTK making graduates as educators, while women's instincts are close to education. So the reason why many women choose the Tarbiyah and Teaching Faculty (FTK) as a place of study is because they want to become educators (teachers). This has resulted in the number of dominant women compared to men at FTK UIN Sunan Ampel. Second, the main motivation for women choosing to study at FTK UIN Sunan Ampel is because they are encouraged to become teachers. Encouragement sometimes arises from oneself, parents, family, or the environment. The majority of women who study at FTK aspire to become teachers. For them the teacher is a world that is close to women's instincts